Structural and optical properties of chlorinated plasma polymers - Turri, Rafael [UNESP]; Davanzo, Celso U.; Schreiner, Wido; Dias da Silva, Jose Humberto [UNESP]; Appolinario, Marcelo Borgatto [UNESP]; Durrant, Steven F. [UNESP] (Elsevier B.V. Sa, 2011)
Amorphous hydrogenated chlorinated carbon (a-C:H:Cl) films were produced by the plasma polymerization of chloroform-acetylene-argon mixtures in a radiofrequency plasma enhanced chemical vapor deposition system. The main parameter of interest was the proportion of chloroform in the feed, R(C), which was varied from 0 to 80%. Deposition rates of 80 nm min (1) were typical for the chlorinated films. Infrared reflection-absorption spectroscopy revealed the presence of C-Cl groups in all the films produced with chloroform in the feed. X-ray photoelectron spectroscopy confirmed this finding, and revealed a saturation of the chlorine content at similar to 47 at.% for R(C)>= 40%. The refractive index and optical gap, E(04), of the films were roughly in the 1.6 to 1.7, and the 2.8 to 3.7 eV range. These values were calculated from transmission ultraviolet-visible-near infrared spectra. Chlorination leads to an increase in the water surface contact angle from similar to 40 degrees to similar to 77 degrees. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Chlorine; IRRAS; XPS; Optical properties